Work-Family Challenges for Low-Income Parents and Their Children. - Crouter, Ann C. (Penn State University family issues symposia series., 2004)
The area of work and family is a hot topic in the social sciences and appeals to scholars in a wide range of disciplines. There are few edited volumes in this area, however, and this may be the only one that focuses on low-income families--a particularly.